Diversity-oriented synthesis of spirothiazolidinediones and their biological evaluation - Kotha, Sambasivarao; Sreevani, Gaddamedi; Dzhemileva, Lilya U.; Yunusbaeva, Milyausha M.; Dzhemilev, Usein M.; D’yakonov, Vladimir A. (Beilstein Journal of Organic Chemistry, 2019)
We report a new synthetic approach to assemble spirothiazolidinediones via a [2 + 2 + 2] cyclotrimerization reaction and the derivatives were further functionalized through DA chemistry and click reaction. Using flow cytometry, it was shown for the first time that the new benzyl alcohol derivatives of thiazolidine-2,4-dione generated here are efficient apoptosis inducers in the HeLa, Hek293, U937, Jurkat, and K562 cell lines.
Keywords: apoptosis; biologically active; [2 + 2 + 2] cycloaddition; flow cytometry; spiro thiazolidinedione

(untitled) - Saini, M. S.; Kumar, A.; Dwivedi, J.; Singh, R. (Int. J. Pharma Sci. Res., 2013)

(untitled) - Arora, P.; Arora, V.; Lamba, H. S.; Wadhwa, D. (Int. J. Pharm. Sci. Res., 2012)

(untitled) - Visentini, P. (Farmaco, Ed. Sci., 1954)

(untitled) - Thompson, L. A.; Ellman, J. A. (Chem. Rev., 1996)

(untitled) - Fujita, T.; Sugiyama, Y.; Taketomi, S.; Sohda, T.; Kawamatsu, Y.; Iwatsuka, H.; Suzuoki, Z. (Diabetes, 1983)

(untitled) - Bruno, G.; Costantino, L.; Curinga, C.; Maccari, R.; Monforte, F.; Nicolò, F.; Ottanà, R.; Vigorita, M. G. (Bioorg. Med. Chem., 2002)

(untitled) - Suzen, S.; Buyukbingol, E. (Curr. Med. Chem., 2003)

(untitled) - Rekha, S.; Shantharam, U.; Chandy, V. (Int. Res. J. Pharm., 2011)

(untitled) - Youssef, A. M.; White, M. S.; Villanueva, E. B.; El-Ashmawy, I. M.; Klegeris, A. (Bioorg. Med. Chem., 2010)

(untitled) - da Rocha Junior, L. F.; de Melo Rêgo, M. J. B.; Cavalcanti, M. B.; Pereira, M. C.; Pitta, M. G. d. R.; de Oliveira, P. S. S.; Gonçalves, S. M. C.; Duarte, A. L. B. P.; de Lima, M. d. C. A.; Pitta, I. d. R.; Pitta, M. G. d. R. (BioMed Res. Int., 2013)

(untitled) - Ip, M. M.; Sylvester, P. W.; Schenkel, L. (Cancer Res., 1986)

(untitled) - Shimazaki, N.; Togashi, N.; Hanai, M.; Isoyama, T.; Wada, K.; Fujita, T.; Fujiwara, K.; Kurakata, S. (Eur. J. Cancer, 2008)

(untitled) - Subtel’na, I.; Atamanyuk, D.; Szymańska, E.; Kieć-Kononowicz, K.; Zimenkovsky, B.; Vasylenko, O.; Gzella, A.; Lesyk, R. (Bioorg. Med. Chem., 2010)

(untitled) - Mulwad, V. V.; Mir, A. A.; Parmar, H. T. (Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem., 2009)

(untitled) - Sharma, R.; Nagda, D. P.; Talesara, G. L. (ARKIVOC, 2006)

(untitled) - Ceylan, M. (Turk. J. Chem., 2006)

(untitled) - Chavan, A. A.; Pai, N. R. (ARKIVOC, 2007)

(untitled) - Albrecht, U.; Gördes, D.; Schmidt, E.; Thurow, K.; Lalk, M.; Langer, P. (Bioorg. Med. Chem., 2005)

(untitled) - Jain, V. S.; Vora, D. K.; Ramaa, C. S. (Bioorg. Med. Chem., 2013)

(untitled) - Singh, S. P.; Parmar, S. S.; Raman, K.; Stenberg, V. I. (Chem. Rev., 1981)

(untitled) - Napoleon, A. A. (Int. J. PharmTech Res., 2016)

(untitled) - Chadha, N.; Bahia, M. S.; Kaur, M.; Silakari, O. (Bioorg. Med. Chem., 2015)

(untitled) - Sohda, T.; Mizuno, K.; Tawada, H.; Sugiyama, Y.; Fujita, T.; Kawamatsu, Y. (Chem. Pharm. Bull., 1982)

(untitled) - Lehmann, J. M.; Moore, L. B.; Smith-Oliver, T. A.; Wilkison, W. O.; Willson, T. M.; Kliewer, S. A. (J. Biol. Chem., 1995)

(untitled) - Brown, F. C. (Chem. Rev., 1961)

(untitled) - Jones, E. R. H.; Robinson, F. A.; Strachan, M. N. (J. Chem. Soc., 1946)

(untitled) - Bozdag, O.; Ertan, R. (Turk. J. Chem., 1999)

(untitled) - Dhara, K.; Paladhi, S.; Midya, G. C.; Dash, J. (Org. Biomol. Chem., 2011)

(untitled) - Okamoto, S.; Sugiyama, Y.-k. (Synlett, 2013)

(untitled) - Shibata, Y.; Tanaka, K. (Synthesis, 2012)

(untitled) - Kotha, S.; Brahmachary, E.; Lahiri, K. (Eur. J. Org. Chem., 2005)

(untitled) - Galan, B. R.; Rovis, T. (Angew. Chem., Int. Ed., 2009)

(untitled) - Chopade, P. R.; Louie, J. (Adv. Synth. Catal., 2006)

(untitled) - Domínguez, G.; Pérez-Castells, J. (Chem. Soc. Rev., 2011)

(untitled) - Gandon, V.; Aubert, C.; Malacria, M. (Chem. Commun., 2006)

(untitled) - Varela, J. A.; Saá, C. (Chem. Rev., 2003)

(untitled) - Yamamoto, Y. (Curr. Org. Chem., 2005)

Cotrimerizations of Acetylenic Compounds - Agenet, N.; Buisine, O.; Slowinski, F.; Gandon, V.; Aubert, C.; Malacria, M. (John Wiley and Sons)

(untitled) - Heller, B.; Hapke, M. (Chem. Soc. Rev., 2007)

(untitled) - Inglesby, P. A.; Evans, P. A. (Chem. Soc. Rev., 2010)

Arene Chemistry: Reaction Mechanisms and Methods for Aromatic Compounds - Tanaka, K. (Transition Metal-Mediated Aromatic Ring Construction, 2016)

(untitled) - Weding, N.; Hapke, M. (Chem. Soc. Rev., 2011)

(untitled) - Vollhardt, K. P. C. (Acc. Chem. Res., 1977)

(untitled) - Paymode, D. J.; Ramana, C. V. (ACS Omega, 2017)

(untitled) - Wakatsuki, Y.; Yamazaki, H. (Tetrahedron Lett., 1973)

(untitled) - Yamamoto, Y.; Kinpara, K.; Saigoku, T.; Takagishi, H.; Okuda, S.; Nishiyama, H.; Itoh, K. (J. Am. Chem. Soc., 2005)

(untitled) - Domínguez, G.; Pérez-Castells, J. (Chem. – Eur. J., 2016)

(untitled) - Kotha, S.; Sreevani, G. (Synthesis, 2018)

(untitled) - Kotha, S.; Mohanraja, K.; Durani, S. (Chem. Commun., 2000)

(untitled) - Kotha, S.; Brahmachary, E. (Bioorg. Med. Chem., 2002)

(untitled) - Kotha, S.; Sreenivasachary, N. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Paladhi, S.; Chauhan, A.; Dhara, K.; Tiwari, A. K.; Dash, J. (Green Chem., 2012)

(untitled) - Kotha, S.; Brahmachary, E. (Tetrahedron Lett., 1997)

(untitled) - Bhat, B. A.; Ponnala, S.; Sahu, D. P.; Tiwari, P.; Tripathi, B. K.; Srivastava, A. K. (Bioorg. Med. Chem., 2004)

(untitled) - Thirumurugan, P.; Matosiuk, D.; Jozwiak, K. (Chem. Rev., 2013)

(untitled) - Wang, Y.-C.; Xie, Y.-Y.; Qu, H.-E.; Wang, H.-S.; Pan, Y.-M.; Huang, F.-P. (J. Org. Chem., 2014)

(untitled) - Xie, Y.-Y.; Wang, Y.-C.; He, Y.; Hu, D.-C.; Wang, H.-S.; Pan, Y.-M. (Green Chem., 2017)

(untitled) - Kotha, S.; Goyal, D.; Bitra, A.; Thota, N.; Kruger, G.; Anand, R. (RSC Adv., 2013)

(untitled) - D'yakonov, V. A.; Tuktarova, R. A.; Dzhemileva, L. U.; Ishmukhametova, S. R.; Yunusbaeva, M. M.; Dzhemilev, U. M. (Steroids, 2018)

(untitled) - Dzhemilev, U. M.; D’yakonov, V. A.; Tuktarova, R. A.; Dzhemileva, L. U.; Ishmukhametova, S. R.; Yunusbaeva, M. M.; de Meijere, A. (J. Nat. Prod., 2016)

(untitled) - Du, K.; Liang, J.; Wang, Y.; Kou, J.; Qian, C.; Ji, L.; Chao, H. (Dalton Trans., 2014)

(untitled) - D'yakonov, V. A.; Kadikova, G. N.; Dzhemileva, L. U.; Gazizullina, G. F.; Yunusbaeva, M. M.; Dzhemilev, U. M. (Tetrahedron, 2018)